2016
DOI: 10.1016/j.neuroscience.2016.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Sigma-1 receptor expression in the dorsal root ganglion: Reexamination using a highly specific antibody

Abstract: Sigma-1 receptor (S1R) is a unique pluripotent modulator of living systems and has been reported to be associated with a number of neurological diseases including pathological pain. Intrathecal administration of S1R antagonists attenuate the pain behavior of rodents in both inflammatory and neuropathic pain models. However, the S1R localization in the spinal cord shows a selective ventral horn motor neuron distribution, suggesting the high likelihood of S1R in the dorsal root ganglion (DRG) mediating the pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 40 publications
4
40
2
Order By: Relevance
“…The marked potentiation of opioid antinociception by peripheral sigma-1 antagonism is consistent with its higher density in the dorsal root ganglion than in several central areas (10). Moreover, these receptors in the dorsal root ganglion are selectively located in sensory neurons and not in glial cells (11). It is now known that sigma-1 receptors can form a macromolecular complex with opioid receptors, tonically inhibiting receptor functioning, and that sigma-1 antagonism can protect opioid receptors from the tonic inhibitory effects of sigma-1 receptors, thus enhancing opioid analgesia (12,13).…”
supporting
confidence: 68%
“…The marked potentiation of opioid antinociception by peripheral sigma-1 antagonism is consistent with its higher density in the dorsal root ganglion than in several central areas (10). Moreover, these receptors in the dorsal root ganglion are selectively located in sensory neurons and not in glial cells (11). It is now known that sigma-1 receptors can form a macromolecular complex with opioid receptors, tonically inhibiting receptor functioning, and that sigma-1 antagonism can protect opioid receptors from the tonic inhibitory effects of sigma-1 receptors, thus enhancing opioid analgesia (12,13).…”
supporting
confidence: 68%
“…Previous work has shown that the Sig‐1R resides in the ER membrane where it is clustered at ER specializations juxtaposed to mitochondria (Hayashi and Su ), and the plasma membrane (Mavlyutov et al. , , ; Wong et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that the Sig-1R resides in the ER membrane where it is clustered at ER specializations juxtaposed to mitochondria (Hayashi and Su 2007), and the plasma membrane (Mavlyutov et al , 2016Wong et al 2016). Additionally, it has been shown that the Sig-1R can translocate to the nuclear envelope upon activation with cocaine, and it has also been reported that the Sig-1R may reside in the PM in dorsal root ganglion (DRG) neurons Tsai et al 2015).…”
Section: Ligand-independent Regulation Of Kv12 By Sig-1rmentioning
confidence: 99%
“…Another possibility is that while the mechanism of action of σ 1R antagonists in pain was first thought to involve a spinal mechanism of action, 21–23 more recent studies suggest an action of DRG neurons where σ 1R is also expressed. 44 It is therefore probable that the time to onset of effects is due to the time that is needed for the drug to diffuse to sites of action that are more distant from the injection site in the intrathecal space. Because σ 1Rs are found on the nuclear envelop of DRG neurons, 44 yet another possibility is that the effect of these compounds is transcriptional.…”
Section: Discussionmentioning
confidence: 99%
“…44 It is therefore probable that the time to onset of effects is due to the time that is needed for the drug to diffuse to sites of action that are more distant from the injection site in the intrathecal space. Because σ 1Rs are found on the nuclear envelop of DRG neurons, 44 yet another possibility is that the effect of these compounds is transcriptional. If this were the case, this would also potentially take longer to manifest as a behavioral change.…”
Section: Discussionmentioning
confidence: 99%